Organ damage in Atlantic herring larvae as a result of ocean acidification. Issue 5 (1st July 2014) - Frommel, Andrea Y.; Maneja, Rommel; Lowe, David; Pascoe, Christine K.; Geffen, Audrey J.; Folkvord, Arild; Piatkowski, Uwe; Clemmesen, Catriona
Abstract : The dissolution of anthropogenically emitted excess carbon dioxide lowers the pH of the world's ocean water. The larvae of mass spawning marine fishes may be particularly vulnerable to such ocean acidification (OA), yet the generality of earlier results is unclear. Here we show the detrimental effects of OA on the development of a commercially important fish species, the Atlantic herring ( Clupea harengus ). Larvae were reared at three levels of CO2 : today (0.0385 kPa), end of next century (0.183 kPa), and a coastal upwelling scenario (0.426 kPa), under near‐natural conditions in large outdoor tanks. Exposure to elevated CO2 levels resulted in stunted growth and development, decreased condition, and severe tissue damage in many organs, with the degree of damage increasing with CO2 concentration. This complements earlier studies of OA on Atlantic cod larvae that revealed similar organ damage but at increased growth rates and no effect on condition.